1994
DOI: 10.1302/0301-620x.76b3.8175853
|View full text |Cite
|
Sign up to set email alerts
|

Screening for congenital dislocation of the hip by physiotherapists. Results of a ten-year study

Abstract: We report a prospective study of the feasibility of employing specially trained physiotherapists to screen neonates for congenital dislocation of the hip. During ten years 42,241 babies were screened, using clinical tests; 255 were diagnosed and treated by a Pavlik harness. In the same period 13 children presented late with congenital dislocation of the hip which had not been detected by the screening programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The rate in the present population was 0.63%, being higher in Jewish infants compared to Arab infants and without cases among infants of Ethiopian origin. These rates are within those reported from Israel as well as from several countries in Europe and in Australia 1,4,6,10–13 . Bialik et al reported in 1986 the results of neonatal clinical screening in Israel, and found a rate of 0.6 % for unstable hips 7 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The rate in the present population was 0.63%, being higher in Jewish infants compared to Arab infants and without cases among infants of Ethiopian origin. These rates are within those reported from Israel as well as from several countries in Europe and in Australia 1,4,6,10–13 . Bialik et al reported in 1986 the results of neonatal clinical screening in Israel, and found a rate of 0.6 % for unstable hips 7 .…”
Section: Discussionsupporting
confidence: 80%
“…Evidence of a dislocatable hip was highly predictive for DDH, and 87% of dislocations were identified shortly after birth. This highlights the importance of clinical screening for these signs as part of routine well‐baby care starting from birth and through infancy 11,15,16 . Senaran et al found that unilateral limitation of hip abduction was a sensitive sign for developmental hip dysplasia 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45] In most maternity hospitals neonatal hip examinations are performed predominantly by paediatricians, or less commonly by orthopaedic surgeons. In order to be accurate and reliable, clinical examination of infant hips must be performed by experienced, trained personnel.…”
Section: Diagnosis Of Hip Dysplasia Clinical Hip Examinationmentioning
confidence: 99%
“…64,65 Additional studies show that well-trained nonphysicians, including physiotherapists and neonatal nurse practitioners, perform at least as well as physician examiners and better than physician trainees. [66][67][68] In 1 single-site longitudinal study, as the number of pediatricians involved in screening infants increased (holding steady the overall number of newborns screened), a greater number of cases of DDH were missed despite an increased rate of suspected cases identified. 69 In other words, both sensitivity and specificity suffered when there was less centralized oversight of the newborn screening program and when fewer infants were screened, on average, by each pediatrician.…”
Section: Key Question 3: What Is the Accuracy Of Screening Tests For mentioning
confidence: 99%